2020
DOI: 10.1016/j.amsu.2020.09.015
|View full text |Cite
|
Sign up to set email alerts
|

Automatic speech recognition in the operating room – An essential contemporary tool or a redundant gadget? A survey evaluation among physicians in form of a qualitative study

Abstract: Introduction For decades, automatic speech recognition (ASR) has been the subject of research and its range of applications broadened. Presently, ASR among physicians is mainly used to convert speech into text but not to implement instructions in the operating room (OR). This study aimed to evaluate physicians of different surgical professions on their personal experience and posture towards ASR. Methods A 16-item survey was distributed electronically to hospitals and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 12 publications
(13 reference statements)
0
5
0
Order By: Relevance
“…Only three studies investigated whether there was an effect of gender on acceptance. None of them found significant effects 50 52 .…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…Only three studies investigated whether there was an effect of gender on acceptance. None of them found significant effects 50 52 .…”
Section: Resultsmentioning
confidence: 89%
“…With respect to age, three studies investigated whether there was an effect of age on the use of AI. Two studies did not observe an effect 50,52 . Walter et al 53 found that 55.8% of younger participants claimed that they would use automated pain recognition.…”
Section: Agementioning
confidence: 93%
See 1 more Smart Citation
“…In addition, patients often require equipment to assist in treatment and rehabilitation. Integrating voice technology into medical equipment can bring great convenience to doctors and patients in many medical scenarios [ 199 ]. For example, smart medicine boxes remind patients to take medicines on time, intelligent ward round systems help doctors collect patient information [ 200 ], and voice systems perform automatic postoperative follow-up visits [ 201 , 202 ].…”
Section: Speech Recognition For Human-medical Equipment Interactionmentioning
confidence: 99%
“…In long-term care for older adults, ASR models have been used to facilitate interview data transcription, saving time and resources [17]. Even in operating rooms, ASR techniques can be used to improve the dialogue between the surgeon and their human (e.g., surgical nurses) or digital (e.g., robotic arms) assistants [18,19]. Additionally, in pediatric care, ASR and voice interaction technologies have been explored for remote care management, demonstrating feasibility and effectiveness in tracking symptoms and health events [20].…”
Section: Introductionmentioning
confidence: 99%